Pemulihan Ekonomi Pariwisata Di Kota Serang Banten Pasca Pandemi COVID 19 - Dzikrullah, Kartini Mega; Moniaga, Natasha Erinda Putri (JURNAL DESTINASI PARIWISATA; Vol 11 No 2 (2023): VOL 11, NO 2 (2023): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2023.v11.i02.p14, 2023)
This article discusses the post-COVID-19 tourism recovery in Serang, Banten. The article highlights the importance of implementing strict health and safety protocols, intensifying marketing efforts, diversifying tourism products, enhancing human resources, fostering collaboration and partnerships, and developing adequate infrastructure. These measures aim to restore Serang City's attractiveness as a tourist destination and stimulate economic growth. By implementing a comprehensive strategy, Serang City can revitalize its tourism sector and make a significant contribution to the local economy. The title of this scientific article was chosen because Tourism in Serang City experienced a decline in visitors during the COVID-19 pandemic, which can be directly analyzed by the author, who is a resident of Serang City. The methodology employed in this writing includes literature study, observation, interviews, and other forms to obtain the most accurate results. The findings of this research aim to identify ways to rekindle tourism interest in Serang, Banten by collaborating with relevant government authorities. Keywords: post-pandemic recovery, tourism sector, marketing, tourism products, collaboration.